Prediking van die Ou Testament in die Christelike Erediens - Robbertze, H. C. G. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2003)
In his interpretation of an Old Testament text, the Christian interpreter must regard the fact of the salvation of Jesus Christ. However, Christian preachers are often quilty of forcing Old Testament texts into a Christian meaning. A legitimate way of discovering the Christian meaning of Old Testament texts is to start with the contextual theology of an Old Testament text. The Christian interpretation of the “original message” must take place in the light of the historical movement of the concerned Old Testament theological line towards its “fulfilment” in the New Testament. The excegetical approaches of Young and Wildberger towards Isaiah 7: 14, as well as Haasbroek’s interpretation of Exodus 19 and the well known work of Bruce Wilkenson on the prayer of Yabes (1 Chronicles 4: 9 - 10) are evaluated in the light of the indicated historical and contextual theological approach to Old Testament texts.